PENATALAKSANAAN FISIOTERAPI PADA KASUS BAYI DENGAN PNEUMONIA KOMUNITAS LOBUS SUPERIOR, SEGMENT ANTERIOR DEXTRA: Physiotherapy Management in Cases of Infants with Community-Acquired Pneumonia in the Right Upper Lobe, Anterior Segment - I Gede Eka Juli Prasana; Ariezta Jeviana; Laili Nuriya Istiani; Ni Made Novi Indah Sari; Ni Kadek Ardya Shinta Alverina; Zainul Muhlisi Mahfud (Forind Press, 2024)
Lower respiratory tract infections are still the main problems in the health sector. Lower respiratory tract infections are the most frequent cause of death in the world. In babies in Indonesia, lower respiratory tract infections are one of the most common causes of death, ranging between 20-30%. Pneumonia is an infection of the lower respiratory tract. Pneumonia is inflammation of the lung parenchyma, the distal part of the terminal bronchioles, namely the respiratory bronchioles and alveoli. Pneumonia results from microbial infections, including bacteria and viruses. or fungi which cause fluid accumulation, consolidation of lung tissue, and impaired air exchange. Pneumonia is characterized by rapid breathing at a certain age limit. Other clinical symptoms include fever, cough, difficulty breathing, accumulation of sputum and shortness of breath. In this study, the problems found in clinical cases hospitalized were shortness of breath and sputum. Intervention of problems found in hospital is with infrared and effleurage massage to reduce muscle spasms, chest physiotherapy and postural drainage help sputum to come out, the effect of which will loosen the airway so as to reduce shortness of breath. Based on the results of providing intervention 5 times in a week, it showed an increase in thorax cage expansion and oxygen saturation, as well as a decrease in respiration rate.